RESEARCH ON THE EVOLUTION OF THE GLOBAL BEEF MARKET IN THE PERIOD 2015-2020 - Irina-Adriana CHIURCIU; Elena SOARE; Paula STOICEA; Carina-Andreea DOBRE; Adina Magdalena IORGA; Aurelia-Vasilica BĂLAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This research captures the changes that took place on the global beef market, for the period 2015-2020. The most representative indicators presented and analyzed are: total cattle herds worldwide; beef and veal production obtained worldwide; beef and veal consumption recorded worldwide; imports and exports recorded worldwide for beef meat. Beef contains a series of proteins, minerals, vitamins, fats and amino acids that recommend it for consumption, because it contributes to maintaining the population health. In 2020, Americas achieved 48.6% of the production of meat of cattle with the bone, fresh or chilled. The most significant consumption per inhabitant of beef and veal was highlighted in Argentina of 36.9 kilograms, in 2020. For the year 2029, the largest consumer of beef and veal is expected to remain also Argentina, with only 36.0 kilograms/capita. The basis of this research was, on the one hand, the statistical data taken from the FAOSTAT website, and on the other hand, the data retrieved from various specialized materials and sites.